(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2018)
The occurrence of Russell’s viper (Daboia russelii Shaw and Nodder 1797) in Bangladesh is century old information and its rarity was known to the wildlife biologists till 2013 but its recent booming is also causing a major threat to human life in the area. Recently it has been reported from nine districts (Dinajpur, Chapai Nawabganj, Rajshahi, Naogaon, Natore, Pabna, Rajbari, Chuadanga and Patuakhali) and old records revealed 11 districts (Nilphamari, Dinajpur, Rangpur, Chapai Nawabganj, Rajshahi, Bogra, Jessore, Satkhira, Khulna, Bagerhat and Chittagong). Thus altogether 17 out of 64 districts in Bangladesh, of which Chapai Nawabganj and Rajshahi are most affected and 20 people died due to Russell’s viper bite during 2013 to 2016. Its past and present distribution in Bangladesh and death toll of its bites have been discussed. Its booming causes have also been predicted and precautions have been recommended. Research on Russell’s viper is deemed necessary due to reemergence in deadly manner. Asiat. Soc. Bangladesh, Sci. 44(1): 15-22, June 2018